2016
DOI: 10.1002/bsl.2221
|View full text |Cite
|
Sign up to set email alerts
|

Projecting Risk: The Importance of the HCR‐20 Risk Management Scale in Predicting Outcomes with Forensic Patients

Abstract: The present study evaluates data from 116 forensic inpatients who underwent violent risk assessments, which included the Historical, Clinical, Risk-20 (HCR-20), from 2006 to 2013 as part of an opportunity to be conditionally discharged from state forensic facilities. Of the 116 inpatients, 58 were never released, 39 were released and returned to a hospital, and 19 were released and never returned. Results from analyses of variance and multinomial logistic regression found the risk management (R) scale of the H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 24 publications
2
12
0
Order By: Relevance
“…In a subsequent study of 116 forensic inpatients who were assessed with the HCR-20 prior to conditional release from state forensic facilities, of which 39 were released and returned, 19 were released but not readmitted, and 58 were not released during the seven year study period. In this study, higher scores on the Risk management scale predicted either non-release, or if released, readmission ( Vitacco et al, 2016 ).…”
Section: Introductionmentioning
confidence: 79%
“…In a subsequent study of 116 forensic inpatients who were assessed with the HCR-20 prior to conditional release from state forensic facilities, of which 39 were released and returned, 19 were released but not readmitted, and 58 were not released during the seven year study period. In this study, higher scores on the Risk management scale predicted either non-release, or if released, readmission ( Vitacco et al, 2016 ).…”
Section: Introductionmentioning
confidence: 79%
“…They reported that all five risk items were associated with a higher likelihood of release, but not the historical and clinical items. They emphasized the importance of clinician recognition of dynamic risk factors to the success of release decisions (Vitacco et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…In a Georgia study, Vitacco, Tabernik, Zavodny, Bailey, & Waggoner (2016) examined the association of HCR-20 items with release decisions. They reported that all five risk items were associated with a higher likelihood of release, but not the historical and clinical items.…”
Section: Decisions By Oversight Boards Regarding Transfer or Releasementioning
confidence: 99%
See 1 more Smart Citation
“…Collectively, these advances hold the potential to provide low-cost and time-efficient assessment procedures that are translatable to a wide array of risk-states. To date, a number of projects have been proposed and evaluated to improve risk assessment of suicide/self-harm (Bridge, Horowitz, & Campo, 2017;Gaynes et al, 2004), homicide/harm-to-others (Vitacco, Tabernik, Zavodny, Bailey, & Waggoner, 2016), psychosis onset and decompensation (Ben-Zeev et al, 2013;Cannon et al, 2016;Carrión et al, 2016), cognitive decline (Harrison et al, 2017) and mania (Hafeman et al, 2017). The potential of these efforts has garnered support from major organizations (Boudreaux & Horowitz, 2014;Cannon et al, 2008aCannon et al, , 2016Heeringa et al, 2013;Hoffmire et al, 2016a;Insel, 2008;Schoenbaum et al, 2014a).…”
Section: The State Of Risk Assessment For Serious Mental Illnessmentioning
confidence: 99%